Ventilatory and heart rate responses to hypoxia and hypercapnia in patients with diabetes mellitus. Issue 4 (April 1989) - Nishimura, M; Miyamoto, K; Suzuki, A; Yamamoto, H; Tsuji, M; Kishi, F; Kawakami, Y
Abstract : The ventilatory response to isocapnic progressive hypoxia and hyperoxic progressive hypercapnia in 24 diabetic patients were compared with those of sex and age matched normal control subjects. The heart rate response to hypoxia was also measured in both groups. In diabetic patients the ventilatory and heart rate responses to hypoxia were significantly lower than those in the control group (0.10 v 0.24 l/min/% fall/m2 and 0.5 l v 1.27 beats/min/% fall respectively). The ventilatory response to hypercapnia was significantly higher (1.09 v 0.76 l/min/mm Hg/m2) in the diabetic patients. There was a significant correlation between the hypoxic ventilatory response and the heart rate response in diabetic patients (r = 0.56), but not in the control group (r = 0.28). In addition, both the ventilatory and the heart rate responses to hypoxia in diabetic patients had weak but significant correlations with the heart rate variation during deep breathing. It is concluded that the ventilatory and heart rate responses to hypoxia in diabetic patients are impaired, whereas the ventilatory response to hypercapnia is well preserved.